The impact of internal entrepreneurship practices on performance: A field study in Jordanian universities - Albaddawi, Eman Awad; Alzoubi, Marwah Mohammed; Alrahahleh, Majed Mohammad (International Journal of Innovative Research and Scientific Studies, 2025)
This study aims to examine the impact of entrepreneurship practices on innovation performance in Jordanian public universities. It also explores how entrepreneurial behaviors and organizational factors contribute to fostering innovation in academic institutions. The study population consists of four major public universities in Jordan: the University of Jordan, Yarmouk University, Al-Hussein Bin Talal University, and Al-Balqa' Applied University. A total of 212 participants comprised the study sample, including 52 faculty members and 160 students from the aforementioned institutions. The research employed a descriptive quantitative methodology using a structured questionnaire adapted from established entrepreneurship and innovation scales. The instrument measured key dimensions such as interactivity, risk-taking, self-renewal, autonomy, and organizational support. Statistical analyses were conducted, including descriptive statistics, Cronbach's alpha for reliability, and analysis of variance for comparison across universities. The results revealed statistically significant differences in entrepreneurship and innovation performance among universities, with the University of Jordan recording the highest average scores across all variables. The results confirmed that entrepreneurship positively impacts innovation performance and that organizational factors play a mediating role. The study recommends strengthening leadership support, enhancing faculty and student autonomy, and developing institutional policies that foster an entrepreneurial culture within universities. These insights contribute to both academic literature and practical policy discussions by highlighting the critical role of entrepreneurship in improving innovation and competitiveness in the Jordanian higher education sector.